Carboxymethyl Cellulose Hydrolyzing Yeast Isolated from South East Sulawesi, Indonesia - Kanti, Atit (Perhimpunan Biologi Indonesia, 2015)
ABSTRACTThe objective of study was to isolate, identify and characterize the CMC-ase producing yeast from South East Sulawesi, Indonesia. We isolated 142 strains and obtain 53 strains (37.32%) were CMC-ase producer consist of 26 species residing within 10 genera. Candida was the most diverse genus consisting of 15 species. It is important to note that several strains residing within this genus could be candidate for new taxa, among others Candida aff. cylindracea PL2W1, Candida aff. insectorum PL3W6, Candida aff. friedrichii MKL7W3, Candida aff. lessepsii, Candida aff. tenuis. Five new candidates for novel species of cellulolytic yeast close to Yamadazyma mexicana: were Yamadazyma aff. mexicana (5 strains). Pichia, Pseudozyma, Sporodiobolus, and Sporobolomyces were other cellulolytic yeasts found in South East Sulawesi. It is obvious, that leaf litter was a good source for cellulolytic yeasts. This CMC-ase producing yeasts dominate this biome, and production of extracellular cellulase is critical strategy for such yeast to survive in cellulose rich ecosystem such as leaf-litter. This finding would suggest that yeasts play key role on hydrolyzes of cellulose and important resources for sustainable energy research. Keywords: cellulolytic yeasts, secondary forest, South East Sulawesi, leaf-litter